Advertising to Early Trend Propagators: Evidence from Twitter - Lambrecht, Anja; Tucker, Catherine; Wiertz, Caroline (Marketing Science, 2018)
In the digital economy, influencing and controlling the spread of information is a key concern for firms. One way firms try to achieve this is to target firm communications to consumers who embrace and propagate the spread of new information on emerging and “trending” topics on social media. However, little is known about whether early trend propagators are indeed responsive to firm-sponsored messages. To explore whether early propagators of trending topics respond to advertising messages, we use data from two field tests conducted by a charity and an emerging fashion firm on the microblogging service Twitter. On Twitter, “promoted tweets” allow advertisers to target individuals based on the content of their recent postings. Twitter continuously identifies in real time which topics are newly popular among Twitter users. In the field tests, we collaborated with a charity and a fashion firm to target ads at consumers who embraced a Twitter trend early in its life cycle by posting about it, and compared their behavior to that of consumers who posted about the same topic later on. Throughout both field tests, we consistently find that early propagators of trends are less responsive to advertising than consumers who embrace trends later. Data and the online appendix are available at https://doi.org/10.1287/mksc.2017.1062 .